Three Cases of Dural Arteriovenous Fistula of the Anterior Condylar Vein within the Hypoglossal Canal - Ernst, Robert; Bulas, Robert; Tomsick, Thomas; van Loveren, Harry; Abdel Aziz, Khaled (American Journal of Neuroradiology, 1999)
Summary: Dural arteriovenous fistulas (DAVFs) of the anterior condylar vein are an uncommon but important subset of fistulas occurring at the skull base that can be confused with DAVFs of the marginal sinus on angiography. MR angiography source images can document the intraosseous extent and the relationship to the hypoglossal canal of this type of fistula, which can have significant clinical implications. We present the imaging features of angiography, CT, and MR angiography of three cases of DAVFs localized to the anterior condylar vein and within the hypoglossal canal, which were confirmed by source images from MR angiography. Transvenous coil embolization was curative in two of three cases and would seem to be the treatment of choice when venous access is available.